70-th anniversary of Fedir Oleksiiovych Ivanyuk - Institute of Nuclear Research (Ядерна фізика та енергетика)
Brief biography and scientific achievements of Fedir Oleksiiovych Ivanyuk in relation with his 70-th anniversary.